Desain dan Implementasi Kotak Pintar (Kopin.COD) Penerima Paket COD dan Paket Non COD Berbasis IoT - Diputra, Muhammad Naufal Airlangga; Saputra, Rizky; Al Gufran, Hasbi Faturrahman; Sulaiman, Habib (JURNAL INTEGRASI, 2025)
This study employs the black-box method and qualitative user analysis. Data collection is conducted through surveys targeting users of the developed tool, aiming to identify common issues in online shopping with the Cash on Delivery (COD) payment method. These issues include customers not being at home when the courier delivers the package, resulting in repeated delivery attempts and delays in receiving packages. Based on this identification, the team determined a solution: creating a smart COD package receiver box integrated with a mobile application, equipped with barcode verification and a surveillance camera. The results show that 98% of users are satisfied with the convenience provided by the Kopin.COD system and feel significantly assisted by this technology. Additionally, survey results from customers or package recipients indicate that 100% of respondents are satisfied with the ease and convenience of use.